RELIGIOUS CIVIL SOCIETY AND CIVIC ENGAGEMENT FROM POLICY TO PRACTICE. SOCIOLOGICAL STUDY AT CAIRO - Khalil, Samah (European Scientific Journal, ESJ, 2013)
Does religious civil society actually exist? Is the increasing in number of registered religious civil society organizations an adequate indication of its existence in the reality? Does the increasing reflect the other increasing in expanding their area of interest to include social responsibility, civic engagement, human rights and religious pluralism within Egypt? According to these questions, the research highlights the cultural, social, economical, political and spiritual activities focusing on how these associations’ views the “other”? How can it perform an intermediary or role between the individual and the society? For achieving that, this research depends on Sociological study for young men Muslim and Christian associations in Egypt in order to take a closer look at these organizations and their programs potential especially towards civic engagement and religious pluralism, It is concluded that there is a lack of associations capable of making equilibrium between cultural identity and religious plurality.